2016
DOI: 10.1142/s021987701750002x
|View full text |Cite
|
Sign up to set email alerts
|

How Do Mobile Information Services Improve Quality of Life? The Case of Japanese Students

Abstract: Every technology should be geared to improve the quality of users’ lives. Our study aims to understand how mobile information services (MIS) contribute to quality of life (QoL) for young mobile users. This paper attempts to provide a comprehensive analysis of relationship between two variables: the contribution of MIS in 15 specific life domains and the contribution of MIS to overall quality of life (QoL). We examined bottom-up spillover theory with original and our additional life domains. Eleven life domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…We found that of our 15 life domains, the following four key life domains had a greater impact on Overall Contribution among young Japanese users than the other significant life domains: Leisure, Cultural, Informational, and Community. The first three, namely, Leisure, Cultural, and Informational life domains are significant, leading to the same stable results as those in [5] for 2015. The last domain, Community Life, became newly significant.…”
Section: Findings and Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…We found that of our 15 life domains, the following four key life domains had a greater impact on Overall Contribution among young Japanese users than the other significant life domains: Leisure, Cultural, Informational, and Community. The first three, namely, Leisure, Cultural, and Informational life domains are significant, leading to the same stable results as those in [5] for 2015. The last domain, Community Life, became newly significant.…”
Section: Findings and Discussionmentioning
confidence: 59%
“…Reference [4] proposed eleven relationships between individual contribution and overall contribution of QoL in Korea and Japan and found that some of them had a stronger influence on overall contribution. Reference [5] analyzed the relationship between MIS and QoL in Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e definition of cloud computing is that a mobile device delivers computing unit storage, operating platforms, other resources, or information service resources, or information service delivery communication networks from the cloud center over the mobile device on demand. is is the combined product of the mobile communication network [11]. Mobile devices connect to the cloud hub over a wireless network and send their own tasks to the cloud hub.…”
Section: Edge Server Deployment Algorithm Design Experimentsmentioning
confidence: 99%
“…Eleven relationships have been proposed [9] between the individual and overall contribution of QoL in Korea and Japan, some of which have been found to have a stronger influence on the overall contribution. Reference [10] and [11] measured the relationship between MIS and QoL of Japanese students, and tested a hypothesis regarding each variable's positive coefficient. Moreover, these studies examined the contribution of life domains to the QoL using MIS based on the bottom-up spillover theory.…”
Section: Introductionmentioning
confidence: 99%